EFEKTIVITAS PENGELOLAAN PIUTANG DAGANG CV MAKMUR SEJAHTERA - Yulius Vandrio Ambut; Ignasius Narew (JURNAL ULET (Utility, Earning and Tax), 2020)
One of the sales systems used by companies is a sales system with credit. The level of sales volume will have a direct impact on increasing the amount of receivables. If receiving receivables is not followed by good insurance management, receivables that are expected to end with receipts are feared to turn into uncollectible receivables. Uncollectible receivables will result in the profits expected by the company. The purpose of this study is to plan the management of receivables. Data were analyzed using receivable turnover ratio, days sales outstanding, total asset turnover, Return On Assets. The results showed that the management of trade receivables at CV Makmur Sejahtera was not effective yet.